Firm bribery and revenue dependence on state-owned enterprises: evidence from a socialist-oriented economy - Khanh Hoang (Cogent Business & Management, 2022)
This study explores the relationship between corporate bribery cost and revenue dependence on contracts from state-owned enterprises (SOEs) in Vietnam, a country with a high level of corruption and a dominant public sector. Using the multiple fixed effect estimator and the entropy balancing technique, our empirical results suggest that firms that depend on contracts from SOEs and the government must bear a higher cost of bribery relative to their counterparts. After clearly classifying firms that depend on SOEs from firms that depend on government contracts, we show that the cost of bribery of SOE-dependent firms is 23.07% higher than average firms. The finding implies general firms pay bribes to SOEs' management to secure their contractual status. Further analysis shows that the effect of revenue dependence on firm bribery cost is sensitive to corruption norms. Our findings provide several implications for policymakers, business strategy, and future research.
Keywords: 650; bribery; corruption norm; rent extraction; revenue dependence; state-owned enterprises